2018
DOI: 10.1002/chir.22855
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective complexation of 1‐phenylethanol with chiral compounds bearing urea moiety

Abstract: A detailed study of diastereomeric complexes of chiral ureido-1,1'-binaphthalene derivatives with chiral 1-phenylethanol showed that a derivative bearing only one urea unit makes five times more stable complex with (S)-enantiomer than with (R)-enantiomer of the alcohol. This phenomenon could be used in chiral discrimination processes. The influence of individual parts of the structure on the complexation properties is shown. The probable structure of diastereomeric complexes based on experimental results and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…S1, ESI†). Compared to acyclic ureido-1,1′-binaphthalenes, 6–8 the NH signals in 1 are significantly shifted to the lower field (9.03 ppm). This feature results from two factors: first, considering the steric demands of the seven-membered ring, the NH-hydrogens stretch out of the cycle in a so-called cis/cis arrangement 18 (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…S1, ESI†). Compared to acyclic ureido-1,1′-binaphthalenes, 6–8 the NH signals in 1 are significantly shifted to the lower field (9.03 ppm). This feature results from two factors: first, considering the steric demands of the seven-membered ring, the NH-hydrogens stretch out of the cycle in a so-called cis/cis arrangement 18 (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…S)-(À)-N-carboxybenzyl-1,1 0 -binaphthalene-2-amino-2 0 -isocyanate (7). Into a three-necked flask was placed protected binaphthalene diamine 6 (0.3 g, 0.72 mmol) dissolved in anhydrous toluene (5 mL), and anhydrous pyridine (0.5 mL, 6.1 mmol, 8.5 equiv.)…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…967 Chiral BINOL-based CSAs with function of Bronsted acids were selected for determination of indoloquinazoline alkaloid-type tertiary alcohols and 3-arylquinazolinones 968,969 and binaphthalene skeleton ureas as sensors for phenylethanol and arylpropanoic acids. 970,971 The BINOL motif is also contained in the amino alcohol 67 recently reported by Lei et al as a CSA for the enantiodifferentiation of carboxylic acids. 972 In this case, the analysis by 1 H NMR spectroscopy demonstrated the excellent enantiodifferentiation ability of 67 toward 14 chiral compounds including both carboxylic acids and non-steroidal anti-inflammatory drugs.…”
Section: Enantioselective Sensingmentioning
confidence: 93%
“…For instance, commercially available (R)-or (S)-BINOL and derivatives as chiral-solvating agents to assign the enantiomeric excess (ee) of enantiomeric hydroxy carboxylic acids, synthetic drugs, natural alkaloids, or flavanones via 1 H NMR spectroscopy (Ardej-Jakubisiak and Kawecki, 2008;Freire et al, 2008;Klika et al, 2010;Redondo et al, 2010Redondo et al, , 2013Chaudhari and Suryaprakash, 2013;Mishra et al, 2014;Yuste et al, 2014;Borowiecki, 2015;Du et al, 2015;Yi et al, 2016;Monteagudo et al, 2017) and bifunctional BINOL-macrocycles containing diacylaminopyridine moieties were developed by Ema et al (2007Ema et al ( , 2008Ema et al ( , 2018; BINOL-derived disulfonimide extends the concept of CSA sensing to chiral recognition of O-heterocycles (Couffin et al, 2014); the crownophane and strapped calix[4]pyrrole containing built-in chiral BINOL were used for the enantioselective recognition of chiral amines and carboxylate anions, respectively (Tokuhisa et al, 2001;Miyaji et al, 2007). Chiral BINOL Brönsted acids were selected for determination of various indoloquinazoline alkaloid-type tertiary alcohols and various 3-arylquinazolinones (Liu et al, 2017;Wu et al, 2018), binaphthalene skeleton ureas as sensor for scanned various sulfoxides, phenylethanol, and arylpropanoic acids (Holakovský et al, 2015;Curínová et al, 2018Curínová et al, , 2019. The results above indicated that highly active binaphthyl scaffold receptors containing multiple binding units could be used as an extremely versatile reagent for various analytes, and the large atropisomeric naphthyl rings also caused shielding effects through π-stacking stabilization that account for enantiomeric discrimination.…”
Section: Introductionmentioning
confidence: 99%